Recycling of polymer films with metal-containing catalyst materials

By hydrothermal treatment without adding organic solvents, the polymer film with a metal-containing catalyst material is recycled, which solves the problems of catalyst insolubleness and polymer inability to recover, and achieves efficient resource recovery and environmental protection.

CN119403945APending Publication Date: 2025-02-07SIEMENS ENERGY GLOBAL GMBH & CO KG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380048503.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-21
Filing Date
2023-06-14
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, when recycling polymer films with metal-containing catalyst materials, there are problems such as catalyst insoluble, polymers cannot be recovered, high process energy consumption, and toxic substances, resulting in waste of resources and environmental pollution.

Method used

The polymer film having a metal-containing catalyst material is recirculated by a hydrothermal treatment method without adding an organic solvent. The catalyst material and polymer material are recovered separately by simultaneously increasing the pressure and temperature in the autoclave, and the liquid and solid phases are formed, and the catalyst material and polymer material are separated by centrifugation.

Benefits of technology

Efficient separation and recycling of catalyst materials and polymer materials is achieved, reducing resource waste and environmental pollution, and reducing energy consumption and complexity of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403945A_ABST
    Figure CN119403945A_ABST
Patent Text Reader

Abstract

The present invention proposes a method (100) for recycling a polymer film having a metal-containing catalyst material. The method has the steps of: S2: applying water without the addition of an organic solvent to a polymer film having a metal-containing catalyst material to form a polymer film-water mixture; s3, simultaneously increasing the pressure and the temperature of the polymer film-water mixture to a pressure between 20 bar and 40 bar and a temperature between 200 DEG C and 250 DEG C to form a liquid phase and a solid phase; and S5, separating the liquid phase and the solid phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a process for recycling a polymer membrane having a metal-containing catalyst material. Background Art

[0002] Hydrogen can be obtained from deionized water by means of electrolysis. This electrolysis can be carried out, for example, as polymer electrolyte membrane electrolysis (PEM electrolysis), in which the reaction chambers for the anodic reaction (I) and the cathodic reaction (II) are separated by means of a membrane that conducts protons (polymer electrolyte membrane, also called proton exchange membrane).

[0003] Anode reaction 2H 2 O→4H + +O 2 +4e - (I)

[0004] The cathode reaction H + +2e - →H 2 (II)

[0005] Polymer electrolyte membranes are usually formed from polymers, in particular ionomers. Perfluorosulfonic acid-containing polymers are often used, which are marketed, for example, under the name Nafion TM Sale.

[0006] Catalyst materials are usually applied to or on the polymer electrolyte membrane in order to be able to perform water electrolysis more efficiently. PEM coated with catalyst materials is also called catalyst coated membrane (catalyst coated membrane), abbreviated as CCM in English. Possible catalyst materials are metals, such as iridium, platinum, ruthenium, palladium in the form of pure metals or metal compounds.

[0007] Similar polymer electrolyte membranes and catalyst materials are used in fuel cells. Unlike the catalyst materials used in fuel cells, the catalyst materials used in water electrolysis usually contain iridium, because iridium is preferably used to catalyze the oxygen evolution reaction (Oxygen Evolution Reaction).

[0008] For example, after expiration of the service life or in the event of faulty production, it is desirable, inter alia for reasons of cost and environmental protection, to recycle the polymer electrolyte membrane together with the catalyst material in order to recover the precious metals and the membrane polymer.

[0009] Recycling methods to date have proposed a two-stage combustion process at temperatures between 850°C and 1000°C, in which HF and CO are released. 2Fluoropolymers are burned in the absence of HF. Due to the aggressive nature of HF, special reactor linings and extensive downstream gas scrubbing are required. The resulting ash is usually mixed with other batches or concentrates and fed to a multi-stage refining process to separate the precious metals. This refining process may in particular provide for the dissolution of the ash in aqua regia (i.e. HCl / HNO in a ratio of about 3:1). 3 mixture).

[0010] However, if a metallic iridium catalyst (Ir0) is used, it cannot be dissolved in aqua regia because metallic iridium is insoluble. Therefore, the subsequent separation process for separating the precious metals includes Na 2 O 2 Oxidative melting process to convert metallic iridium into soluble IrO 2 This process only results in low yields and must be performed several times.

[0011] A significant disadvantage of the established process chains is the loss of the catalysts used, since these are completely dissolved and have to be reprecipitated or powdered. Due to the large number of process steps, process side streams are generated which represent potential loss paths, since they can only be brought into the main process stream with great effort.

[0012] Furthermore, the membrane polymer cannot be recovered, since it is burned in the initial combustion process. Moreover, the entire recycling method is also energy-intensive and time-consuming. Furthermore, due to the use of a variety of chemicals, a series of toxic substances are formed, which must be specially handled and constitute a risk factor for the workers involved in the recycling as well as for the environment.

[0013] A kind of alternative recycling method is disclosed by document US 7 255 798 B2, wherein the CCM to be recycled is subjected to treatment in a water-solvent mixture at elevated pressure and elevated temperature. As solvent, methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, 2-methoxyethanol, 2-ethoxyethanol, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, dioxane, acetonitrile or a mixture of the mass fraction of the mentioned solvent between 10% and 80% can be used. After this treatment, the catalyst material and the polymer material can be separated from each other and further processed. For example, a membrane can be prepared again from the polymer material, and the catalyst material can be deposited on the membrane.

[0014] A disadvantage of this process is that a mixture of water and organic solvent is used, since this makes the purification of the recycled polymer and catalyst material more difficult. In addition, the organic solvents used are hazardous substances, thereby increasing the potential risk to the personnel involved in the recycling and to the environment, especially in the context of process conditions of elevated pressure and temperature. Summary of the invention

[0015] Against this background, the object of the present invention is to specify a method for recycling a polymer membrane provided with catalyst material, with which the above-mentioned problems can be reduced or even completely avoided.

[0016] This object is achieved by the subject matter of the independent claim. The dependent claims relate to preferred embodiments of the solution according to the invention.

[0017] The present invention relates to a method for recycling a polymer membrane with a metal-containing catalyst material. The method comprises the following steps: subjecting the polymer membrane with the metal-containing catalyst material to water without the addition of an organic solvent to form a polymer membrane-water mixture; simultaneously increasing the pressure and temperature of the polymer membrane-water mixture to a pressure between 20 bar and 40 bar and a temperature between 200° C. and 250° C., wherein a liquid phase and a solid phase are formed; and separating the liquid phase and the solid phase.

[0018] The polymer membrane with the metal-containing catalyst material can be, for example, a polymer electrolyte membrane for water electrolysis or for use in a fuel cell. The polymer membrane can, for example, comprise polymerized perfluorosulfonic acid as the polymer material or the polymer material can, for example, consist of polymerized perfluorosulfonic acid.

[0019] In addition to the polymer material, the polymer membrane also has a metal-containing catalyst material, which is used, for example, to catalyze the anode reaction (I) and / or cathode reaction (II) in the water electrolysis mentioned at the beginning, or to catalyze the anode reaction and / or cathode reaction in a fuel cell using hydrogen as fuel. The metal-containing catalyst material may contain one or more noble metals selected from the group consisting of iridium, platinum, ruthenium, rhodium and palladium, each in the form of a metal compound (e.g. metal oxide) or in the form of a pure metal.

[0020] The method step of increasing the pressure and temperature simultaneously can be carried out, for example, as a hydrothermal treatment in an autoclave. A pressure in the range between 20 bar and 40 bar and a temperature in the range between 200° C. and 250° C. must be achieved simultaneously at least once. The specific treatment duration depends in particular on the chemical composition of the polymer material and the size of the polymer film block to be treated. The holding time can be, for example, 5 to 15 minutes, for example 10 minutes. The hydrothermal treatment favors the slippage of the polymer chains, so that the polymer material dissolves in water.

[0021] Preferably, the temperature may be increased to a temperature between 220° C. and 230° C. When the temperature is higher than 250° C., the polymer may have begun to decompose, and when the temperature is lower than 200° C., the polymer may not be sufficiently dissolved.

[0022] For example, the liquid phase and the solid phase can be separated by centrifugation, preferably at a rotation speed of 10,000 to 15,000 rpm. The metal-containing catalyst material and / or the metal of the metal-containing catalyst material can then be recovered from the separated solid phase.

[0023] The separated liquid phase contains the dissolved polymer, which, depending on the concentration, can be further utilized directly or after concentration. In the described process, concentration is particularly advantageous because, due to the use of water as solvent without the addition of organic solvents, different boiling points, such as in the case of water-alcohol mixtures, do not need to be taken into account.

[0024] By separating the polymer and the metal-containing catalyst material from each other, the proposed method enables the recycling of the polymer membrane, in particular the polymer electrolyte membrane, and the metal-containing catalyst material contained therein and / or deposited thereon. This allows the recovery and reuse of the polymer and / or the metal-containing catalyst material after a further recycling step, if necessary.

[0025] Since both polymer materials and metal-containing catalyst materials are scarce and cost-intensive materials, recycling is advantageously associated with conservation of resources and cost savings. Compared to the combustion method explained at the outset, the proposed method has the advantage that in addition to recovering the metal-containing catalyst material, the polymer material can also be recovered. Both the metal-containing catalyst material and the polymer material can be recovered without significant losses and in a substantially unchanged state, so that they can be directly integrated back into the value creation chain. Compared to conventional combustion processes with downstream precious metal refining, this brings additional cost advantages and resource savings. In the method described here, the number of process steps is significantly reduced, namely from about 20 process steps with recycling by combustion to about six process steps, whereby loss paths, in particular loss paths for iridium, can be avoided. The reprocessing costs for separation (separation process) and the preparation costs for precipitating new catalyst material are omitted.

[0026] The recycling process is performed without the use of organic solvents, ie, for example, without the addition of alcohols, carboxylates, ethers, ketones, alkanes, aromatic hydrocarbons, glycol ethers and nitriles. For example, the polymer film-water mixture can be formed by applying distilled water without adding any additives.

[0027] This simplifies the purification of the recycled, ie recovered, polymer and catalyst material. Furthermore, the potential risk to the personnel involved in the recycling and to the environment is reduced. In particular, the safety when carrying out the method can be increased due to the increased temperature and the increased pressure.

[0028] Mainly in view of the amount of platinum catalyst, it is particularly advantageous to carry out the treatment in water without adding organic solvent. Otherwise, the platinum catalyst may react with the organic solvent and there may be safety risks. In addition, as mentioned above, it will be significantly facilitated to subsequently concentrate the polymer solution.

[0029] Optionally, the polymer membrane with the metal-containing catalyst material can be broken up into fragments, for example, with a size between 1 mm and 10 mm, preferably between 2 mm and 5 mm, before the water is applied. The breaking up can be carried out, for example, by cutting or chopping.

[0030] The fragmentation has the advantage that a more homogeneous polymer film-water mixture is formed, whereby the hydrothermal treatment can be carried out more efficiently, ie, for example, the holding time can be reduced, or the continuous process execution can be simplified.

[0031] According to various embodiment variants, the polymer membrane may have a fiber reinforcement. In this case, the method may comprise separating the fibers of the fiber reinforcement before separating the liquid phase and the solid phase.

[0032] The fibers can be in the form of a support structure and, for example, comprise polyetheretherketone (PEEK) or consist of polyetheretherketone (PEEK). The fibers can be separated, for example, by means of a sieve, for example by using a sieve with a mesh size of 0.1 mm to 0.3 mm.

[0033] By separating the fibers, it is possible to prevent the fibers from being retained in the solid phase, thereby obtaining a solid phase with a higher purity of the metal-containing catalyst material. This makes it possible to avoid downstream purification of the metal-containing catalyst material for removing the fibers or components thereof.

[0034] According to a further embodiment variant, the method can have the step of recovering the separated solid phase.

[0035] If desired, different metal-containing catalyst materials or the metals contained therein, for example metallic iridium and platinum or platinum-containing compounds, can be separated from one another.

[0036] The further processing can have one or more physical and / or chemical process steps, for example treatment with aqua regia, filtration, precipitation by addition of precipitants, washing and the like.

[0037] The specific choice of the recovery step depends on the metal-containing catalyst material present and the desired one or more recycle products. The recovery of the separated solid phase serves to recover the metal-containing catalyst material in metallic form and / or chemically bound form, preferably enabling direct reuse, for example as catalyst material for water electrolysis or for catalysis in a fuel cell.

[0038] For example, the separated solid phase can be reprocessed to obtain metallic iridium, for example in the form of a powder, so-called iridium black. Since iridium-containing raw materials are particularly limited and obtaining iridium is complicated and wasteful, the recovery of metallic iridium is particularly advantageous.

[0039] According to a further embodiment variant, the method can include treating the separated liquid phase with activated carbon.

[0040] The activated carbon treatment enables very small particles, for example of metal-containing catalyst material, to be removed from the separated liquid phase, which particles cannot be separated by means of centrifugation.

[0041] The purity of the remaining aqueous polymer solution can thereby be increased, so that after a possible concentration the polymer solution can be processed further directly without further purification.

[0042] According to a further embodiment variant, the method can include producing a polymer membrane from the separated liquid phase.

[0043] The separated liquid phase has an aqueous solution of the polymer material of the polymer film. From this solution, a polymer film can be produced again, for example by forming a layer from the liquid phase, for example on a carrier material, and subsequently drying and optionally thermostatting. For this purpose, coating methods can be used which form a coating from a liquid phase, for example spin coating, dip coating, film drawing with a doctor blade.

[0044] Optionally, the separated liquid phase can be concentrated before applying the liquid phase. For this purpose, water can be removed, for example, by means of rotary evaporation. Further optionally, before rotary evaporation, n-propanol can be added to the liquid phase, for example, in a mass ratio of water to n-propanol of 3:7. The use of n-propanol is preferred because its boiling point is close to that of water. As a result, the crosslinking of the polymer can be increased during the drying of the deposited layer, thereby promoting the subsequent formation of the film and, if necessary, the properties of the resulting film can be specifically influenced. In order to avoid cracks during the subsequent film drawing, it is helpful to draw the solvent evenly, because this allows the polymer chains to be evenly crosslinked and evenly adjacent to each other. Otherwise, the hydrophobic parts of the polymer main chain may form micelles with n-propanol in an undesirable manner, and the hydrophilic side chains may form micelles with water.

[0045] Preferably, the polymer film can be re-produced from the recycled polymer film, thereby avoiding the generation of waste and conserving resources.

[0046] Of course, it is also possible to mix new polymer material with recycled polymer material for the production of polymer membranes.

[0047] According to a further embodiment variant, the polymer membrane-water mixture can be stirred during the step of simultaneously increasing the pressure and the temperature.

[0048] The stirring speed may be, for example, 50 to 400 rpm.

[0049] The advantage of stirring is that a more homogeneous polymer film-water mixture can be formed, thereby allowing the hydrothermal treatment to be performed more efficiently, ie, for example, by shortening the holding time, or by simplifying the execution of a continuous process.

[0050] According to a further embodiment variant, at least the step of simultaneously increasing the pressure and the temperature can be performed continuously.

[0051] Preferably, further method steps can be performed continuously, such as crushing the polymer membrane with metal-containing catalyst material, subjecting the polymer membrane with metal-containing catalyst material to water without added organic solvent, separating the fibers of the fiber reinforcement of the polymer membrane, recovering the separated solid phase, and / or treating the separated liquid phase with activated carbon.

[0052] By performing the process continuously, higher yields can be achieved, thereby allowing for more efficient recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] The characteristics, features and advantages of the present invention described above and the methods for achieving them will be more clearly understood in conjunction with the following description of the embodiments, which will be explained in more detail in conjunction with the accompanying drawings. Among them:

[0054] Figure 1 A flow chart showing an exemplary method for recycling a polymer membrane having a metal-containing catalyst material;

[0055] Figure 2 A pressure-temperature diagram illustrating conditions during hydrothermal treatment is shown;

[0056] Figure 3 shows a graph illustrating the ion exchange capacity of new polymer membranes and polymer membranes prepared from recycled polymer material; and

[0057] Figure 4 Shown is a graph illustrating the equivalent molecular weight of new polymer membranes compared to the equivalent molecular weight of polymer membranes prepared from recycled polymer materials. DETAILED DESCRIPTION

[0058] Figure 1 A flow chart of an exemplary method 100 for recycling a polymer membrane with a metal-containing catalyst material is shown. This embodiment relates to recycling a perfluorosulfonic acid polymer membrane with a PEEK support structure and a metal-containing catalyst material. A 40 g membrane-electrode unit (Silyzer 300 module) with a platinum catalyst on the cathode from water electrolysis is used as the starting material.

[0059] After the start of the method 100 , the polymer membrane with the metal-containing catalyst material is comminuted into pieces with a size of about 3 mm in method step S1 . For this purpose, a comminution machine of the machine type Moco ZG 10 with an output of 200 kg / h is used.

[0060] Subsequently, in method step S2 , 235 g of deionized water (without addition of organic solvents or other additives) were applied to the cut segments, thereby forming a polymer film-water mixture.

[0061] In method step S3, the polymer film-water mixture is subjected to a hydrothermal treatment, in which the pressure and temperature are increased simultaneously. In the exemplary embodiment, a laboratory autoclave with a volume of 700 ml is used for this purpose, but continuous process execution is also possible. In the exemplary embodiment, the hydrothermal treatment is carried out for 10 minutes at a temperature of 225° C. and a pressure of 24 bar. During the hydrothermal treatment, the perfluorosulfonic acid polymer goes into solution, whereupon foam forms on the resulting solution and the viscosity of the solution increases compared to water.

[0062] Figure 2 A diagram is shown from which possible pressure-temperature conditions for carrying out method step S3 can be derived. Typically, the pressure must be between 20 bar and 40 bar, and the temperature between 200° C. and 250° C. In an embodiment, the hydrothermal treatment is carried out at a temperature of 225° C. and a pressure of about 23-24 bar.

[0063] See again Figure 1 After the hydrothermal treatment, the method 100 continues with method step S4, in which the PEEK fibers that did not enter the solution during method step S3 are separated. For this purpose, a coarse mesh screen with a mesh size between 0.1 mm and 0.3 mm is used. If the polymer membrane does not have a fiber reinforcement, method step S4 can be omitted.

[0064] In method step S5, the solid phase and the liquid phase formed after the hydrothermal treatment are separated from each other. In this case, the solid phase has the metal-containing catalyst material, while the perfluorosulfonic acid polymer is dissolved in the liquid phase. The phase separation is carried out by centrifugation at a speed of 11,500 rpm for 1 hour. After the phase separation, the solid phase and the liquid phase are processed further separately.

[0065] The solid phase is recovered in method step S6, which is divided into steps S6a to S6e in the execution step. For this purpose, in step S6a, aqua regia is added to the solid phase and the temperature is raised to about 80° C. This allows the platinum contained to go into solution and can be separated by filtration in step S6b. In step S6c, the platinum precipitates or precipitates out of the filtrate. In step S6d, the filter residue is washed with deionized water until a pH value of 7 is reached. After drying in step S6e, metallic iridium is obtained in the form of a powder, which can be used as a catalyst again and directly, i.e. without further conversion steps or purification steps.

[0066] For further processing of the liquid phase obtained in method step S5, an optional treatment with activated carbon is carried out in method step S7. Here, the polymer solution, ie the ionomer phase, is clarified. After separation of the activated carbon, a purified aqueous solution of the perfluorosulfonic acid polymer is obtained.

[0067] In method step S8, a polymer membrane is re-prepared from the obtained aqueous perfluorosulfonic acid polymer solution. Method step S8 is divided into steps S8a to S8c.

[0068] The production of a polymer film from a recycled polymer is carried out from a thermocompressed polymer solution. In method step S8a, the polymer solution is concentrated in a rotary evaporator at a negative pressure between 60 mbar and 80 mbar and a temperature of a hot bath of 40° C., wherein two different solvent formulations are tested. In one case, the polymer solution is purely concentrated in a rotary evaporator by extracting water from the solvent. In this case, a large amount of foaming of the polymer solution may occur. In another case, n-propanol is added to the polymer solution in a ratio of 3:7 of water to n-propanol before the rotary evaporation. Since the perfluorosulfonic acid polymer is easily soluble in water, but water is highly polar after all, the addition of another solvent enables the perfluorosulfonic acid to crosslink during the drying process.

[0069] In the next step S8b, the film from the concentrated solution is pulled onto a polyimide foil (Kapton foil) with the aid of a scraper. The scraper has a moving speed of 10 mm / s. In step S8c, the pulled film is dried at 60° C. for 30 min in a drying oven and then isothermally treated at 180° C. for 10 min. A polymer film without visible defects is obtained. In order to characterize the obtained polymer film, its ion exchange capacity and equivalent molecular weight are determined.

[0070] The recycling of polymer membranes should not result in damage to the polymer. The material properties of polymer membranes prepared from recycled polymers should roughly correspond to the properties of polymer membranes prepared from new, i.e. first-time used polymer material. In order to characterize polymer membranes prepared from recycled polymer material, the ion exchange capacity IEC and the equivalent molecular weight which can be calculated therefrom were determined. The results are summarized below and are graphically shown in Figure 3 and Figure 4 middle.

[0071] Figure 3 The ion exchange capacity of polymer membranes produced from recycled polymer material (labeled "IEC rec.") and the ion exchange capacity of polymer membranes produced from new polymer material (labeled "IEC new") are shown in comparison, respectively, in the case of membranes produced from aqueous solutions (right side of the bar graph) and in the case of membranes produced from n-propanol-water mixtures (ratio of water to n-propanol = 3:7, left side of the bar graph). For polymer membranes produced from recycled polymer material, the error bars recorded represent the actual distribution of the measured values ​​in five test samples, whereas for polymer membranes produced from new polymer material, the error bars recorded represent the range of the predetermined manufacturer's specifications.

[0072] according to Figure 3 The comparison of shows that the ion exchange capacity of the polymer membranes produced from the recycled polymer material is within the lower range of the specifications of the polymer membranes produced from the new polymer material. In other words, recycling only insignificantly negatively affects the ion exchange capacity.

[0073] In addition, Figure 3 It can also be concluded that the ion exchange capacity of polymer membranes prepared from recycled polymer material is slightly higher when prepared from aqueous solution than when prepared from n-propanol-water mixture, while when new polymer material is used, the ion exchange capacity does not depend on whether the membrane is prepared from aqueous solution or from n-propanol-water mixture.

[0074] In addition, the ion exchange capacity was converted into the equivalent molecular weight EW of the polymer membrane (IEC = (V (NaOH) * c (NaOH)) / m0, unit mmol / g; EW = 1000 / IEC, unit g / mol), and they were plotted relative to each other on Figure 4(the designation "rec. n-propanol / water" corresponds to polymer membranes made from recycled polymer material prepared from n-propanol-water mixtures; "rec. water" corresponds to polymer membranes made from recycled polymer material prepared from aqueous solution, and "new" corresponds to polymer membranes made from new polymer material, with values ​​being independent of whether prepared from aqueous solution or from n-propanol-water mixtures). Comparison of the equivalent molecular weights of the polymer membranes indicated that the values ​​for the recycled membranes were within the manufacturer's specifications and that there was no structural damage to the polymer caused by recycling.

[0075] It was therefore determined that the membranes produced from recycled perfluorosulfonic acid polymer material by means of the described method do not have damage to the perfluorosulfonic acid polymer caused by the recycling process.

[0076] In summary, the following advantages are associated with the proposed method:

[0077] - The recovery rate of precious metals is high, above 95%,

[0078] - Iridium catalysts were obtained, eliminating the need for re-synthesis,

[0079] - ionomer dispersions suitable for preparing new membranes are obtained,

[0080] - Mild process conditions,

[0081] - No harmful emissions,

[0082] -Chemical recycling process that takes care of raw materials,

[0083] - Simple process chain without special process technology,

[0084] - allows direct replacement of the previous combustion process step to recover precious metals and simultaneously recover other valuable substances, such as polymer films,

[0085] -Through efficient use of raw materials, emissions can be reduced and the availability of scarce catalyst metals can be ensured.

[0086] The proposed method is also suitable for the reprocessing of a large number of polymer membranes with metal-containing catalyst materials.

[0087] Although the present invention has been illustrated and described in detail by means of preferred embodiments, the present invention is not limited to the disclosed examples, and those skilled in the art may derive other variations from these examples without departing from the scope of protection of the present invention.

[0088] As used herein, the term "and / or" when used in conjunction with a series of two or more elements means that each of the listed elements may be used alone or every combination of two or more of the listed elements may be used.

Claims

1. A method (100) for recycling a polymer membrane having a metal-containing catalyst material, the method comprising the following steps: - S2: subjecting the polymer membrane with the metal-containing catalyst material to water without the addition of an organic solvent to form a polymer membrane-water mixture, - S3: The pressure and temperature of the polymer membrane-water mixture are simultaneously increased to a pressure between 20 bar and 40 bar and a temperature between 200° C. and 250° C., wherein: Formation of liquid and solid phases, and - S5: separating the liquid phase and the solid phase.

2. The method (100) according to claim 1, wherein: The metal-containing catalyst material has one or more noble metals selected from the group consisting of iridium, platinum, ruthenium, rhodium and palladium.

3. The method (100) according to any one of the preceding claims, comprising: - S1: Disintegration of the polymer membrane with the metal-containing catalyst material before application of water.

4. The method (100) according to any one of the preceding claims, comprising: - S4: separation of the fibres of the fibre reinforcement of the polymer membrane before separation of the liquid phase and the solid phase.

5. The method (100) according to any one of the preceding claims, comprising: - S6: Recovering the separated solid phase.

6. The method (100) according to claim 5, wherein: In the step of recovering the solid phase, metallic iridium is obtained.

7. The method (100) according to any one of the preceding claims, comprising: - S7: The separated liquid phase is treated with activated carbon.

8. The method (100) according to any one of the preceding claims, comprising: - S8: Preparation of a polymer membrane from the separated liquid phase.

9. The method (100) according to any one of the preceding claims, wherein: The polymer film-water mixture is agitated during the step of simultaneously increasing pressure and temperature.

10. The method (100) according to any one of the preceding claims, wherein: At least the steps of simultaneously increasing the pressure and the temperature are performed continuously.

11. The method (100) according to any one of the preceding claims, wherein: Polymer membranes with metal-containing catalyst materials are polymer electrolyte membranes for water electrolysis or for use in fuel cells.

12. The method (100) according to any one of the preceding claims, wherein: The polymer film includes a perfluorosulfonic acid polymer.

13. The method (100) according to any one of the preceding claims, wherein: In the step of simultaneously increasing the pressure and temperature of the polymer membrane-water mixture, the temperature is increased to a temperature between 220°C and 230°C.

Citation Information

Patent Citations

  • Recycling of used perfluorosulfonic acid membranes

    US7255798B2